Students’ Mathematical Thinking Solving Math Story Problems - Meira Indria Pratiwi; Susiswo Susiswo; Santi Irawati (PRISMA, 2025)
Mathematics story problems are important to learn because they relate to contextual life. In the preliminary study, many MTs Qita Malang students made mistakes. One way to find out students' mistakes is to explore how they think mathematically. Therefore, the researcher conducted a study that aimed to describe how students think mathematically in solving mathematical story problems. The instruments used were test sheets and interview guidelines. This research is a qualitative-descriptive research that was attended by 15 grade IX students of MTs Qita Malang. Three research subjects were selected based on their ability level (high, medium, low). The results showed that students were highly capable through all aspects in the entry and attack phases, but missed the check and extend aspects in the review phase. Moderately capable students go through all aspects in the entry phase and skip the why aspect in the attack phase and only succeed through the reflect aspect in the review phase. Low ability students go through the entry phase of the know and want aspect, but skip the maybe and why aspect in the attack phase, and only through the reflect aspect in the review phase.